The automatic roof with sensor by using solar energy / Nik Muhammad Syahzwan Nik Roslan, Nur Aliaa Anisah Rohizad and Nur Ain Shafiqah Azidin - Nik Roslan, Nik Muhammad Syahzwan; Rohizad, Nur Aliaa Anisah; Azidin, Nur Ain Shafiqah (2015)
For a working couple, it is hard to find time to have laundry day where the cloth is dried through the whole day because the weather can change from sunny to rainy days. This projects use Microcontroller Arduino Uno to install all program that will give instructions to conduct this system properly. This project will automatically retrieve-in the awning when it is the sunny day and oppositely retrieve-out the awning when it is a rainy day. This part needs DC motor to convert electrical power into mechanical power for retrieve-out and retrieve-in all the awning. Temperature sensors that will be used in this project can measure temperature and day condition whether it is sunny or rainy day more accurately.